INHIBITION OF Vibrio harveyi BY MENIRAN (Phyllanthus niruri L.) LEAF EXTRACT IN LABORATORY TESTS - Zalfi Eka Yanti; Frida Alifia; Sri Rukmini; Ardi Eko Mulyawan (Universitas Mataram, 2026)
Vibrio harveyi is a Gram-negative bacterium that causes vibriosis in shrimp, which can inhibit growth and trigger mass mortality in the larval phase. Various natural compounds such as flavonoids, alkaloids, saponins, and tannins are known to be able to suppress the growth of pathogenic bacteria. Phyllanthus niruri L. leaves have the potential to be antibacterial because they contain various bioactive compounds. This study aims to determine the effect of meniran leaf extract in inhibiting the growth of Vibrio harveyi bacteria. This research method used a Completely Randomized Design (CRD) with the concentration of meniran leaf extract (Phyllanthus niruri L.) in treatments A, B, C, D, E, and F of 0 ppm, 5,000 ppm, 10,000 ppm, 15,000 ppm, 20,000 ppm and Oxytetracycline 30µ (control), replications 3 times. The results showed that all treatments of meniran leaf extract were able to inhibit the growth of Vibrio harveyi bacteria (P < 0.05). The highest inhibitory diameter was obtained by treatment E, namely 13.41 mm, followed successively by D at 12.57 mm; C at 11.29 mm; and the lowest in treatment B at 9.43 mm. Based on ANOVA analysis, meniran leaf extract significantly inhibited Vibrio harveyi bacteria.